To burn or not to burn? A case study of the unburned farm in the community of São Sebastião do Livramento-Cutias/AP (Research, Society and Development, 2021)
With the aim of investigating the use of fire in rural community in Amapá, characterizing the productive models, of alternative family farmers, understanding how they construct a change in the production model, as well as reproduce their empirical knowledge. Agricultural properties were assessed between August and September 2019. The study had as strategy the "exploratory research," carried out through questionnaire with 20 farmers. The data obtained was tabulated, analyzed and grouped with Microsoft Excel 2010 ® and Minitab filter. The system of overthrow and burning still adopted. The change in farmer practices on land use has been gradually changed. The option for fire use is related to cost reduction in cleaning the productive area. Of the 85% of farmers surveyed, they reported that they do not use fire as a cleaning technique, but data differ from information obtained through satellite imaging. The culture of cassava is one of the main ones. Farmers (90%) know the advantages of ash for plants and soil. As for the disadvantage of fire (55%) say they have knowledge, however it was observed, that they do not know the Legislation. Techniques to avoid deforestation and burns such as: use of the same area by stew, ploughing and grading, in addition to care such as soil conservation, rotating crops with legumes, direct planting and more productive varieties, were also observed. It is necessary that public policies be implemented, aiming to reduce the cost of recovery of the area with sustainable and cheaper practices.